Five dimensions of climate governance: a framework for empirical research based on polycentric and multi-level governance perspectives - Deborah Heinen; Alessandro Arlati; Jörg Knieling (Environmental Policy and Governance, 2021)
Governance of climate mitigation and adaptation has been discussed within polycentric and multi-level governance perspectives. Both perspectives on climate governance are intimately related but yet in some regards are distinctly different - as one perspective has evolved from empirical research within the United States and the other in the European Union. Within an increasingly global discourse on climate governance, there is a need in the literature to bring both discourses together. The findings are based on a systematic literature review of 42 climate governance papers published since 2000. This paper discusses how multi-level and polycentric climate governance perspectives converge and diverge along five dimensions. The five dimensions provide insights for applying a multi-level or polycentric governance perspective to empirical research.
Keywords: 330; analytical framework; climate governance; decision-making; multi-level governance; polycentric governance